Integrated neuropsychological and cognitive behavioural therapy after acquired brain injury: A pragmatic randomized clinical trial. Issue 7 (9th August 2022) - Exner, Cornelia; Doering, Bettina K.; Conrad, Nico; Künemund, Anna; Zwick, Sarah; Kühl, Kerstin; Nestler, Steffen; Rief, Winfried
ABSTRACT: After acquired brain injury (ABI) many patients suffer from persistent cognitive and emotional disturbances. The aim of this study was to investigate the treatment outcome of an integrated intervention, combining neuropsychological and cognitive behavioural therapy (nCBT), against waitlist (WL) in outpatients with ABI. Individuals seeking outpatient treatment for cognitive and emotional problems after ABI were randomly allocated to nCBT ( n = 27) or WL ( n = 29) and completed assessments at baseline, post-treatment/WL and at six-month follow-up. The primary outcome measures were general psychopathology and functional activity in daily life. The nCBT group showed significant improvement for general psychopathology post-treatment when compared to WL. nCBT was also superior to WL regarding the secondary outcomes, i.e., the reduction of negative affect and the improvement of quality of life. No significant differences for functional activity and community integration were observed. Significant pre–post effect sizes ranged between small for functional activity and medium for quality of life. The positive effects were maintained at follow-up. The majority of patients with cognitive and emotional problems after ABI benefit from an integrated approach that offers cognitive remediation and psychotherapy. However, the heterogeneous sequelae of ABI and the moderate sample sizes in clinical trials present a methodological challenge to ABI research.